Measurement of the degradation of abandoned turf - Varga, Krisztina; Csízi, István (Acta Agraria Debreceniensis, 2019)
With the decreasing number of grazing livestock in Hungary, the role of the turf cultivation is also significantly decreasing. The proportion of the under- and non-utilized turf is increasing. In the research conduced at the University of Debrecen, IAREF Research Institute Karcag, we studied four types of turf utilization in three replicates on a salt field with timothy grass. We determined the flora composition of the experimental area, measured the soil moisture and the carbon-dioxide content of the soil.